The Effect of Income and Tax Knowledge upon Taxpayer Compliance in Paying Land and Building Tax in Pulutan Village - Christopher Siwi; Stanny S. Rawung; Maya Salindeho (International Journal of Applied Business and International Management, 2020)
This study aims to determine the effect of income and tax knowledge upon taxpayer compliance in paying Land and Building Tax in Pulutan Village. This study made use a quantitative approach with 75 samples. Data were collected through questionnaires and documentations. The results of the study were analyzed with multiple linear regression analysis. This study indicates that: (1) there is a positive and significant effect of income on tax compliance in paying Land and Building Tax in Pulutan Village; (2) there is a positive and significant effect of tax knowledge on tax compliance in paying Land and Building Tax in Pulutan Village; (3) there is a positive and significant effect of income and tax knowledge on tax compliance in paying Land and Building Tax in Pulutan Village.